Application of Active Cycle of Breathing Technique for Patient with Corona Virus at Respiratory Isolation Unit: An Interventional Study - Haider Mizher Fenjan, Khalida Mohammed Khudur (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Active Cycle Breathing Techniques is a technique of breathing exercises that contributes as a rehabilitative lung therapy, and helps to improve readings of body physiological variables such as oxygen saturation rate, heart rate, respiratory rate and Burke scale. Aims: The current study aims to assess the effect of the active course of breathing techniques on patients with coronavirus in the respiratory isolation unit, evaluate the educational program of the active course of breathing techniques on patients with coronavirus in the respiratory isolation unit, in addition to finding the relationship between the effect of active courses of breathing technology on patients with coronavirus. And their social demographic characteristics represented by age, gender, educational level, marital status, occupational status, and area of residence. Methodology: The design of one group pre-test and post-test, the study was conducted on a non-probability-objective sample consisting of forty patients infected with Corona virus in Yousef Hospital for Isolation in Al-Muthanna Governorate. The statistical methods that were applied using the statistical package for social sciences were adopted, Version 26.0. Results: The results indicated that the ACBTs achieved a significant improvement in the patients’ parameters, and the educational program significantly improved the knowledge and practices of ACBTs at (0.05˂P) after 5 days of the intervention. Conclusion: Active breathing exercise is effective in improving respiratory parameters, especially the effect on oxygen saturation (spo2), heart rate, respiratory rate, and Borg scale (measurement of dyspnea) among coronavirus patients. It helps mobilize the secretions and helps re-expand lung tissue. On the other hand, the research contributed to providing an educational program that strengthened and enriched the knowledge and practices of patients in benefiting from this technology at the level of health care and in their daily lives. Recommendations: It is recommended to use the active cycle of breathing techniques at least once or more, depending on the patient’s condition, with an emphasis on the use of this technique in addition to other physiotherapy techniques. To teach patients about the active course of breathing techniques to improve their knowledge and practice.